In search of the author: narrative voice in Svetlana Aleksievich's Chrnobyl'skaia molitva - Burenius, Clas Axel (2019)
Svetlana Aleksievich is a contemporary Belarusian author whose works straddle the divide between Soviet and post-Soviet time. Based on tape-recorded interviews with eyewitnesses to events of historical and political significance, such as the Chornobyl’ nuclear disaster and the Soviet-Afghan war, her works can be considered a hybrid form of journalism and fiction. This form of writing, where the statements of a multitude of individuals are selected, processed and arranged by a single author, raises important questions about representation and authorial agency. Focusing on Aleksievich’s fifth book, Chernobyl’skaia molitva: khronika budushchego (Chernobyl Prayer: A Chronicle of the Future) [1985], this MA thesis examines the unresolved tension between the voices of the eyewitnesses and that of Aleksievich. Its aim is firstly to contextualise and conceptualise the question of authorial agency in Aleksievich’s writing in general, and secondly to examine the concrete textual manifestations of authorial agency in Chernobyl’skaia molitva. The thesis will explore the extent to which Chernobyl’skaia molitva displays a clear political bias through the ideological position that its implied author occupies in relation to the narrators. Moreover, it will show that in its thematic insistence, Chernobyl’skaia molitva presents a specific eco-critical perspective on the nuclear accident, a particular interpretation of the relationship between the Soviet state and its citizens, and a specific view on issues related to the possibilities of language to adequately communicate an experience – points which, contrary to the implicit assertion of the text of being the product of a multitude of authors, can only be attributed to a single consciousness. Thus, this thesis argues that Chernobyl’skaia molitva performs two separate functions: “giving a voice” to the witnesses of the event and, through these voices, presenting a particular “message” or “worldview”.